Postcolonial violence: narrating South Africa, May 2008 - Sandwith, Corinne (2011)
The violent attacks on immigrants in May and June 2008 laid bare some of the contradictions of the South African postcolony. Focusing on the vigorous public debate which arose in the aftermath of violence, this essay explores a moment of interpretive crisis in which the privileged stories of the nation were unexpectedly unravelled. From there, it moves to a discussion of the political investments at stake in the government’s choice of the ‘crime story’ as dominant interpretive scheme, giving particular emphasis to what this revealed about national myth-making, the production of consensus and modalities of power in the postcolonial state.